Study of the Reinforcement Effect in (0.5–x)TeO2–0.2WO3–0.1Bi2O3–0.1MoO3–0.1SiO2–xCNDs Glasses Doped with Carbon Nanodiamonds - Artem L. Kozlovskiy; Indira Tleulessova; Daryn B. Borgekov; Vladimir V. Uglov; Viktor M. Anishchik; Maxim V. Zdorovets; Dmitriy I. Shlimas (Nanomaterials, 2022)
The purpose of this study is to examine the influence of carbon nanodiamonds on the reinforcement and hardening of telluride glasses, as well as to establish the dependence of the strengthening properties and optical characteristics of glasses on CND concentration. According to X-ray diffraction data, the synthesized glasses have an amorphous structure despite the addition of CNDs, and at high concentrations of CNDs, reflections characteristic of small crystalline particles of carbon nanodiamonds are observed. An analysis of the strength properties of glasses depending on the concentration of the CND dopant showed that an increase in the CND concentration to 0.10–0.15 mol. leads to an increase in hardness by 33–50% in comparison with undoped samples. The studies carried out to determine the resistance to external influences found that doping leads to an increase in the resistance of strength characteristics against destruction and embrittlement, and in the case of high concentrations, the change in strength properties is minimal, which indicates a high ceramic stability degree. The study of the radiation resistance of synthesized glasses found that the addition of CNDs leads to an increase in resistance to radiation damage when irradiated with gamma rays, while also maintaining resistance to high radiation doses. The study of the shielding characteristics found that the addition of CNDs is most effective in shielding gamma rays with energies of 130–660 MeV.